Pengaruh Brand Image Produk Handphone Nokia Terhadap Keputusan Pembelian Konsumen (Studi Kasus pada Mahasiswa Jurusan Administrasi Niaga Politeknik Negeri Sriwijaya) - Paisal Paisal (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2011)
Purpose of this final report is to determine the effect of brand image against the decisions of consumers in purchasing products nokia in commercial administration student at the polytechnic Sriwijaya Palembang. Author would like to know the extent of brand image the most dominant influence purchasing decisions and influence whether or not that level of purchase decision. Data used is the purchase decision, which is the dependent variable (Y) and perceptions of consumers based on six levels on the brand image which is the independent variable (X), which is an attribute (x1), benefits (x2), value (x3), personality (x4), culture (x5) and owner (x6).Analysis of data using questionnaire method. The result of demonstrating the value of R square influencing the purchase decision on nokia mobile products for 53.4%. For 53.4% of purchase decisions are influenced by the six levels of brand image and the remaining 46.6% influences include other factors beyond this study. Level of brand image the most dominant influence purchasing decisions is the level of the owner (x6). Based on the results of the study, the authors suggested that more attention to the sixth level of the company's brand image, especially at the level of brand image that does not affect the purchasing decision.Keywords: Brand Image, Purchasing Decisionse